2020
DOI: 10.18203/2349-2902.isj20204679
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of successful trial with-out catheter following acute urinary retention secondary to benign prostatic hypertrophy

Abstract: Background: Acute urinary retention (AUR) is one of the most psychologically distressing complications of benign prostatic hypertrophy (BPH). Attempt of trial without urinary catheter (TWOC) is given to all these patients, failing which they are subjected to surgical management. This study was conducted to analyse the possible predictors of successful trials in such patients.Methods: Patients reporting to our centre with a first episode of spontaneous AUR secondary to BPH were enrolled. Following per-urethral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Regarding another medication frequently used in BPH, 5-ARI, several studies have demonstrated that in addition to the effect on prostatic volumetry, this therapeutic class also proves its effectiveness by reducing the microvascular density of the prostatic parenchyma, thus resulting in a decrease in bleeding intraoperatively during transurethral prostate resection as well as postoperatively, significantly reducing the probability of macroscopic haematuria [ 17 ]. No research has been conducted on the utility of 5-ARI in TWOC.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding another medication frequently used in BPH, 5-ARI, several studies have demonstrated that in addition to the effect on prostatic volumetry, this therapeutic class also proves its effectiveness by reducing the microvascular density of the prostatic parenchyma, thus resulting in a decrease in bleeding intraoperatively during transurethral prostate resection as well as postoperatively, significantly reducing the probability of macroscopic haematuria [ 17 ]. No research has been conducted on the utility of 5-ARI in TWOC.…”
Section: Discussionmentioning
confidence: 99%